2017
DOI: 10.1371/journal.pone.0173756
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-205-5p is correlated to metastatic potential of 21T series: A breast cancer progression model

Abstract: MicroRNA is a class of noncoding RNAs able to base pair with complementary messenger RNA sequences, inhibiting their expression. These regulatory molecules play important roles in key cellular processes including cell proliferation, differentiation and response to DNA damage; changes in miRNA expression are a common feature of human cancers. To gain insights into the mechanisms involved in breast cancer progression we conducted a microRNA global expression analysis on a 21T series of cell lines obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Many studies demonstrate that prostate cancer cell lines and tumor cells exhibit suppressed miR-205 levels [ 24 ]. miR-205 loss is highly associated with tumor growth, invasion, and migration of cancer cells [ 25 ]. The reconstitution of miR-205 effectively inhibits proliferation of prostate cancer cells ( Figure 3 D) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies demonstrate that prostate cancer cell lines and tumor cells exhibit suppressed miR-205 levels [ 24 ]. miR-205 loss is highly associated with tumor growth, invasion, and migration of cancer cells [ 25 ]. The reconstitution of miR-205 effectively inhibits proliferation of prostate cancer cells ( Figure 3 D) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used isogenic primary 21PT and metastatic 21MT-2 cell lines, which were derived from the same HER2 positive patient at different tumor stages [ 51 53 ]. 21PT are noninvasive cell line and represent infiltrating ductal carcinoma with carcinoma in situ component, which represent early stage of breast cancer, whereas 21MT-2 is a metastatic cell line and is derived from pleural effusion of lung metastasis [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-205-5p was also predicted to target genes responsible for breast cancer invasiveness, including SOCS3 , PTPRN2 , and MMP3 , and also genes associated with EMT regulatory functions, such as TGFB1 . Therefore, this work showed that miR-205-3p may serve as a key player during progression of a tumor to an invasive, metastatic phenotype [148].…”
Section: Micrornas and Breast Cancer Progressionmentioning
confidence: 99%